The Legal Dilemmas of the Drinking Water Supply in the Republic of Slovenia - Štemberger Brizani, Katja (Central European Academy Law Review, 2025)
Slovenia is one of the few European countries where the right to drinking water is explicitly recognised by the highest legal act. It was included in the Constitution of the Republic of Slovenia in 2016 (Article 70a), but it was constitutionally protected even before that (under the right to life, personal dignity, and the right to a healthy living environment). Although the explicit recognition of this right at the highest level is important, it raised many dilemmas that have not yet been (fully) resolved. Specifically, the constitutional law has excluded the possibility of providing drinking water in the private sector, i.e. through concessions, while the sectoral legislation governing water concessions has not (yet) been amended, which creates an anomaly in the legal order. In this respect, the question of the permissibility of (retroactive) interference with already granted concessions may also arise. Furthermore, the constitutional law has interfered with the (original) competences of municipalities by stipulating that drinking water supply shall be provided by the state, through self-governing local communities, directly and on a non-profit basis. This implies that the provision of drinking water is no longer the original competence of the municipalities, but of the state. However, it is not clear on what legal basis the municipalities shall provide it or how its financing shall be organised. In addition, defining the provision of drinking water as ‘non-profit’ may raise questions as to the nature of this activity (economic or non-economic public service) and its compliance with EU law. Notwithstanding all the above, the legislator has still not aligned (all) legislation with the new Article 70a, despite the 18 month deadline set by the constitutional law. All this shows that the inclusion of this right in the Constitution has more of a political than a legal nature.